Corporate hedging and default risk: a multinational perspective - Le, Khai (2025)
This thesis discusses three topics regarding hedging by non-financial companies and its impact on default probability with insights from a multinational analysis. The first paper investigates the impact of derivatives on firm’s default probability with a sample of European non-financial firms. The second paper studies the influence of currency hedging strategies with foreign exchange derivatives and foreign debts on default risk. The third paper examines the effect of long-term and short-term interest rate derivatives on the likelihood of default. The first paper explores the influence of the use of derivative on the risk of default among non-financial firms with a cross-country approach. By using a unique sample of hand collected derivative usage of non-financial firms in nine different European countries, including the UK, France, Germany, Denmark, Italy, Norway, the Netherlands, Spain and Sweden, over the period of 1999 to 2015, our findings suggest that derivative hedging reduces default probability. Our study also shows that the reduction of default risk is more intensive under the use of interest rate (IR) derivatives compared to foreign exchange (FX) and commodity (CP) derivatives. Additionally, our paper records evidence that derivative usage has a statistically bigger negative influence on short-term than long-term default risk. The negative correlation of derivatives and default risk stays robust after performing a wide range of robustness test for possible endogeneity emerging from derivative usage and probability of default. Moreover, our study documents some new evidence that firms with extremely high financial distress may hedge less, as evidenced by the increase in default likelihood. As for the role of creditor rights on the effect of derivative use toward default risk, our results support the notion that firms would hedge more and reduce more risk in countries where creditor protection is strong. Furthermore, we present findings indicating that the efficacy of derivatives diminishes in the presence of lower economic risk within a country. In the second paper, we investigate the effect of different currency hedging strategies, from foreign exchange (FX) derivatives and foreign currency (FC) debt, used by non-financial firms on default probability with a sample of non-financial firms in six countries including France, Germany, Italy, Norway, Spain and the United Kingdom from 1999 to 2015. Our results show that hedging with FC debt does not reduce and may even increase default probability. Furthermore, generally, we find that linear derivative strategies (FX forwards or swaps) reduce probability of default better than a non-linear strategy (FX options), contrary to our expectation. However, we record that non-linear strategy is more optimal, in terms of default risk reduction, for firms with high growth, whereas low growth firms benefit more from linear strategies. In addition, our results show that currency forwards reduce short-term default likelihood better than swaps, while currency swaps impact more on long-run default risk. Moreover, we document evidence that the effect of foreign debt on default risk is more positive as debt enforcement is more efficient. Interestingly, our findings demonstrate that FC debt could be an effective tool for reducing the likelihood of default, especially for companies operating in countries with weak debt enforcement efficiency and a significant proportion of foreign sales. The empirical analysis employs a battery of robustness tests to control for dynamic endogeneity issues. These findings extend our knowledge of the risk reduction effects of various hedging methods. The third paper compares the effectiveness of long-term (swaps) and short-term IR derivatives (forwards and options) in reducing default risk for non-financial firms in Germany, France, Spain, Italy, Denmark, Sweden, the Netherlands, Norway and the UK for the period from 1999 to 2015. Interestingly, we find that IR swap contracts are more effective than their short-term counterparts (IR forwards and options) in managing both short and long-term default probability. This could be explained by the fact that long-term derivatives are designed to hedge firm’s total exposure, both short and long term. However. we document evidence that firms in countries which promote the use of short-term liabilities can benefit more, in terms of default risk reduction, from the use of short-term derivatives. In particular, German and Spanish firms that rely more intensively on short-term liabilities experience a larger decrease in the likelihood of default by using short-term IR derivatives compared to long-term contracts. In addition, our findings show that among the short-term derivatives, IR option derivatives reduce the probability of default more effectively than IR forwards. We also document evidence that firms of medium size tend to exhibit a more pronounced reduction in their default probability using IR swaps, while the impact on default risk is insignificant for the smallest and largest firms, potentially due to factors such as less access to derivative markets for small firms and access to fixed-rate borrowing options for large firms. Overall, our findings are novel and able to deliver significant contribution to corporate hedging literature.